"It breaks your soul": An in‐depth exploration of workplace injustice in nursing. (10th January 2018) - Skinner, Natalie; Van Dijk, Paul; Stothard, Christina; Fein, Erich C.
Abstract : Aim(s): To understand nurses' experiences of injustice in the workplace and to identify the impact of injustice on well‐being. Background: Little is known about how nurses view injustice or its effects on their well‐being, although research indicates that such perceptions are central to workplace practices such as performance management and outcomes such as employee well‐being. Method(s): A qualitative study was conducted with semi‐structured interviews for nurses employed in Australian public hospitals. Data were analysed using content analysis. Results: Experiences of injustice and unfairness negatively impacted on performance and the personal health of nurses. Unfair treatment was met with reduced effort and commitment. Conclusion(s): This study provides valuable insights into how nurses perceive and experience injustice at work and supports the link between injustice and nurses' decreased well‐being and effectiveness. Implications for Nursing Management: Implications for nurse managers include the need for managers to engage in regular conversations regarding systemic barriers to performance and implementing performance management as an ongoing dialogue designed for employee voice and relationship management. This process also suggests a need for leadership development in nursing management. Using such steps and strategies would significantly enhance best practice in nursing management.